Human resource management : (McGraw-Hill, 2006)
This book represents a valuable approach to teaching human resource management for several reasons: The text draws from the divese research, teaching and consulting experiences of four authors. They have taught human resource managment...Human resource management is viewed as critical to the success of a business. The book discusses current issues such as e HRM finding and keeping talented employees, diversity. Strategic human resource management is introduced early in the book and integrated throughout the text...